2014
DOI: 10.3945/an.113.004788
|View full text |Cite
|
Sign up to set email alerts
|

Economic Benefits and Costs of Human Milk Feedings: A Strategy to Reduce the Risk of Prematurity-Related Morbidities in Very-Low-Birth-Weight Infants

Abstract: Infants born at very low birth weight (VLBW; birth weight <1500 g) are at high risk of mortality and are some of the most expensive patients in the hospital. Additionally, VLBW infants are susceptible to prematurity-related morbidities, including late-onset sepsis, bronchopulmonary dysplasia (BPD), necrotizing enterocolitis, and retinopathy of prematurity, which have short- and long-term economic consequences. The incremental cost of these morbidities during the neonatal intensive care unit (NICU) hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 29 publications
1
66
0
10
Order By: Relevance
“…A recent analysis confirmed that human milk costs are minimal compared with the costs of the major morbidities in very low birth weight infants. 17 The results of this analysis indicate a significant effect on overall mortality as well as sepsis that was not identified in the individual studies previously reported. 4,5 The combined studies demonstrate a dose-related effect of nonhuman milk intake in increasing negative patient outcomes.…”
Section: Discussionmentioning
confidence: 60%
“…A recent analysis confirmed that human milk costs are minimal compared with the costs of the major morbidities in very low birth weight infants. 17 The results of this analysis indicate a significant effect on overall mortality as well as sepsis that was not identified in the individual studies previously reported. 4,5 The combined studies demonstrate a dose-related effect of nonhuman milk intake in increasing negative patient outcomes.…”
Section: Discussionmentioning
confidence: 60%
“…Among these 'interventions', breast feeding is considered to be the most cost-effective, especially for lowbirthweight (LBW) infants (Stevenson and Cooke, 1998;St John et al, 2000;Phibbs and Schmitt, 2006;Jegier et al, 2010;Johnson et al, 2014). The World Health Organization (WHO) endorses breast feeding as the most efficient nutritional practice for the health and well-being of preterm infants (WHO/UNICEF, 1990, 1992.…”
Section: Introductionmentioning
confidence: 99%
“…While there is literature to support this conclusion in preterm and very low-birthweight neonates, there is a paucity of literature assessing the role of BM diets on outcomes of neonates who do not meet such criteria. 5,[7][8][10][11][12][13][14] The objective of this study was to assess whether a diet of ‡50% BM is associated with an earlier transition off of PN in neonates with specific GI disorders when compared to similar neonates who receive enteral diets <50% BM. Secondary outcomes included hospital LOS and days to achievement of full enteral feeds.…”
Section: Introductionmentioning
confidence: 99%